Hubungan Dukungan Sosial Keluarga dengan Kenakalan Remaja - Mudeska, Romi Wardey; Ilyas, Asmidir (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2015)
Ideally a teenager in an achievement school who is seen with high learning outcomes according to the KKM, can adjust to the social environment, behave according to the norms that apply in the social environment of the community, not endanger themselves, and not harm others materially. But the reality in the field is that there are still teenagers who cannot adjust to the social environment, there are teenagers who do not behave according to the norms that apply in society, there are still teenagers who do not excel in school, there are teenagers who endanger themselves, and there are teenagers who materially harm others. Therefore this study aims to describe the family social support, juvenile delinquency, and how the family's social support relationship with juvenile delinquency. This type of research is descriptive correlational which aims to find facts in accordance with the actual situation. The research subjects were 30 students of class VII, VIII and IX of SMP Negeri 1 Sungai Pua, Sungai Pua District, Agam District, West Sumatra. The instruments of data collection were questionnaires for family social support and juvenile delinquency questionnaires using a Likert scale. Data was processed using descriptive statistical analysis techniques and to test the relationship of data was analyzed using the Pearson Product Moment formula with the Statical Product and Service Solution (SPSS) program version 16.0. The results of this study reveal that: (1) family social support is in the high category, (2) juvenile delinquency students are in the low category. (3) there is a significant negative relationship between family social support and juvenile delinquency in Sungai Pua State Middle School 1 Sungai Pua District, Agam District, West Sumatra with a significant value of 0.002. Based on the findings of this study, it is expected that BK teachers or counselors can provide assistance in the form of Counseling Guidance services.Keywords: Family Social Support, Juvenile Delinquency